Analisis keperluan pembinaan modul pengajaran pendidikan akhlak mualaf Selangor bagi strategi penyampaian pengajaran - Siti Fatkhiah Jamadi; Jaffary Awang; Zul ‘Azmi Yaakob (Penerbit Universiti Kebangsaan Malaysia, 2024)
Education is the main core in shaping noble moral character in the hearts of converts, and character is an important asset in Islam. The need for moral education for the converted group requires the study of constructing comprehensive moral education teaching modules, including suitable teaching delivery strategies so that the converted group receives continuous guidance. This article focuses on the analysis of the need to identify moral issues and problems among converts in the compulsory convert religious classes (KFAM) at the Selangor Zakat Board (LZS) and also identifies the need for the construction of modules for teaching moral education for converts in Selangor for the teaching delivery strategy element. Needs analysis is one of the important phases in the data collection process to obtain input on the need for the construction of a module. The research design is in the form of qualitative research focusing on document analysis. Two elements have been identified, (i) the approach to teaching module delivery methods based on the Quran and Hadith moral education approach and moral education according to Islamic scholars, and (ii) innovation in the formation of convert moral education teachers involving aspects of mastery of basic teaching knowledge, comparative religion knowledge, and psychology knowledge. The findings of this study provide positive implications for teachers to improve teaching and learning methods through suitable Islamic moral education theories tailored to the background of students as converts. The findings of the study also provide an important indicator for further research, which is to design and develop moral education teaching modules for converts in Selangor.